Voluntary disclosure of financial ratios: evidence from portuguese listed companies - Batista, Inês de Figueiredo Tavares (2017)
While financial ratios are a useful tool to provide financial information, their disclosure remains mostly voluntary. This Work Project studies the extent, presentation and determinants of voluntary disclosure of financial ratios in the annual reports of 43 Portuguese listed companies. Results show that, on average, ratio disclosure is low, there is great disparity in terminology and there is some discrepancy in presentational features. Only the external auditor being one of the Big Four is significantly associated with higher disclosure. These conclusions alert to the need for tighter guidelines on extent, computation and presentation of financial ratios voluntarily disclosed.